Approaches to describing and analyzing classroom communication - Aleksandrzak, Magdalena (Glottodidactica, 2013)
The article discusses some selected approaches to classroom communication and addresses the problem of its authenticity. The complexity of the subject, together with the multiplicity of the models, interpretations and research methodologies used in the process of data collection and analysis contribute to the fact that classroom discourse is generally regarded as a problematic and demanding research area which requires a multi-dimensional approach and a well-grounded choice of analytic framework.